2021
DOI: 10.1007/s40596-021-01541-9
|View full text |Cite
|
Sign up to set email alerts
|

Stigma in Psychiatry: Impact of a Virtual and Traditional Psychiatry Clerkship on Medical Student Attitudes

Abstract: Objective The objective of the study was to assess the change in medical students’ attitudes towards psychiatry following a virtual clerkship experience compared to a traditional clerkship experience. Method Ninety-seven medical students from the University of Ottawa were assessed pre- and post-clerkship on the ATP-30 (Attitudes Towards Psychiatry-30) measure. Cohorts of students were categorized as pre-COVID or during-COVID depending on when and how they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…These students provided informed consent. This latter sample was part of a separate project that has since been published [ 20 ] and was incorporated into this analysis to serve as a comparison to the OPEP students. The University of Ottawa Office of Research and Integrity provided ethics approval and approved all experimental methods for use of these data.…”
Section: Methodsmentioning
confidence: 99%
“…These students provided informed consent. This latter sample was part of a separate project that has since been published [ 20 ] and was incorporated into this analysis to serve as a comparison to the OPEP students. The University of Ottawa Office of Research and Integrity provided ethics approval and approved all experimental methods for use of these data.…”
Section: Methodsmentioning
confidence: 99%
“…Four articles in the December 2021 issue of Academic Psychiatry [3,4,7,8] add to the existing literature on medical student attitudes toward psychiatry worldwide. "Revisiting the ATP 30: The Factor Structure of a Scale Measuring Medical Students' Attitudes Towards Psychiatry" [4] reexamines the ATP-30 [5], which was originally found to have no meaningful subscales.…”
mentioning
confidence: 99%
“…Finally, in "Stigma in Psychiatry: Impact of a Virtual and Traditional Psychiatry Clerkship in Medical Student Attitudes" [8], the ATP-30 is utilized to examine changes in attitudes toward psychiatry in a virtual versus in-person clerkship experience. Although the authors admit that existing literature has not revealed a consensus on the "influential nature clerkships have on students and their attitudes toward psychiatry as a specialty," they hypothesized that the virtual model would have a detrimental impact on attitudes.…”
mentioning
confidence: 99%